Prevalence of Common Mental Disorders in South Asia: A Systematic Review and Meta-Regression Analysis - Sadiq Naveed; Ahmed Waqas; Amna Mohyud Din Chaudhary; Sham Kumar; Noureen Abbas; Rizwan Amin; Nida Jamil; Sidra Saleem (Frontiers in Psychiatry, 2020)
South Asian countries report the highest prevalence of common mental disorders (CMDs) globally. This systematic review and meta-analysis report the pooled prevalence of CMDs among the South Asian countries. Database searches were conducted in eight electronic databases. Titles, abstracts, full-text screening, and extraction of data on the event rate of 17 indicators of CMDs were performed by two independent reviewers. A total of 160 studies were included and data analysis was done using the Comprehensive Meta-analysis Software (v.3). A prevalence of depressive symptoms was 26.4% among 173,449 participants, alcohol abuse was 12.9% (n = 107,893); anxiety 25.8% (n = 70,058); tobacco smoking 18.6% (n = 84,965); PTSD 17.2% (n = 42,298); mixed anxiety and depression 28.4% (n = 11,102); suicidal behaviors 6.4% (n = 25,043); misuse of opiates 0.8% (n = 37,304); tobacco chewing 21.0% (n = 10,586); use of cannabis 3% (n = 10,977); GAD 2.9% (n = 70,058); bipolar disorder 0.6% (n = 7,197); IV drug abuse 2.5% (n = 15,049); panic disorder 0.01% (n = 28,087); stimulant use 0.9% (n = 1,414); OCD 1.6% (n = 8,784) and phobic disorders 1.8% (n = 27,754). This study reported a high prevalence of CMDs in South Asian countries; necessitating further research on psychiatric epidemiology in those contexts. It informs the need for effective policymaking and implementation of culturally appropriate multilevel interventions.